2020
DOI: 10.1521/pedi.2020.34.5.609
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Resting-State Brain Networks and Unique Variability of Conduct Problems Within the Externalizing Dimension

Abstract: The externalizing psychopathological dimension is associated with alterations in adolescents’ functional brain connectivity. The current study aims to identify the functional correlates of the unique variability in conduct problems within the context of the broad externalizing dimension. The broad externalizing dimension and unique variability in conduct problems were estimated using a bifactor model. Resting-state data were available for a sample of 125 adolescents. Based on multiresolution parcellation of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Likewise, negative brain connectivity score was mainly represented by brain regions of the Salience, VentAttn and Cingulo-Opercular networks such as the dACC and bilateral vlPFC and aINS. Dysconnectivity in these networks were found to be associated with the broad dimension of externalizing pathology in two recent studies ((66) and ABCD study:(67)) which corroborates our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, negative brain connectivity score was mainly represented by brain regions of the Salience, VentAttn and Cingulo-Opercular networks such as the dACC and bilateral vlPFC and aINS. Dysconnectivity in these networks were found to be associated with the broad dimension of externalizing pathology in two recent studies ((66) and ABCD study:(67)) which corroborates our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast with the functional decoding suggesting their implications in reward processing tasks, we recently found that antisocial subjects exhibited reduced brain activity in these regions (i.e., pg- & dACC extending to the aMCC/pre-SMA as well as the aINS) during acute threat response ( Dugré et al, 2020 ). Moreover, recent studies support the association of functional brain dysconnectivity at a region-level (i.e., aINS-pgACC & pgACC-Supramarginal Gyrus, see Afzali et al, 2020 ) and a network-level (i.e., increased salience-ventral attention connectivity, see Lees et al, 2021 ) with broad externalizing problems. In our study, we observed that CP was negatively associated with functional connectivity of brain regions underpinning Cingulo-Opercular network (i.e., aINS, lPFC, SMA) and those corresponding to visual (i.e., Area 2 and lingual gyrus), Auditory (i.e., Heschl gyrus) and unlabeled (i.e., Lateral OFC).…”
Section: Discussionmentioning
confidence: 83%
“…This problem, which is referred to as a granularity mismatch between behavioural and biological measures 134 , should be considered carefully and can be addressed by taking a hierarchical approach to behavioural assessment. We thus advocate for a 'splitting' approach, in which psychopathological constructs are dissected into finer-grained, lower-order homogenous constructs to isolate specific variance while taking account of the hierarchical organization of these phenotypes [135][136][137][138] . The study conducted by Tiego et al (2022) 139 provides an example of a splitting approach that identified significant associations between polygenic risk for schizophrenia and psychometric measures of schizotypy in a non-clinical sample that were otherwise obscured by the use of raw scores or a lumping approach.…”
Section: Use Of Homogenous Unidimensional Scalesmentioning
confidence: 99%